Alternative grading practices: An entry point for faculty in competency‐based education. Issue 3 (23rd July 2020) - Townsley, Matt; Schmid, David
Abstract: Due to a lack of buy‐in from multiple stakeholder groups, institutions of higher learning may struggle to reorient their entire course and program offerings to embrace the full breadth of competency‐based education. One such way of overcoming these systematic issues to make incremental progress toward competency‐based education is to consider practices such as grading that single professors can implement without the need of full institutional support. Few college instructors are likely to have received any formal grading training. As such, they may rely on institutional norms and their personal experiences as students. In response to historical grading challenges in higher education, some faculty members have adopted models working against the status quo such as mastery grading, specifications grading, and standards‐based grading, which all promote students demonstrating their learning on criterion‐referenced tests in a more flexible time frame. The purpose of this paper is to describe alternative forms of grading as an entry point for faculty incrementally progressing toward competency‐based education axioms in higher education. The authors recommend a multiple‐step course design framework and areas for future research.